2019
DOI: 10.1177/2158244019835951
|View full text |Cite
|
Sign up to set email alerts
|

The English Communication and Learning Needs of Master of Business Administration Students and Curriculum Development at a Chinese University

Abstract: This study investigates the communication and learning needs of Master of Business Administration (MBA) business English students and their perceptions of effective curriculum design. The research instruments are two-stage surveys of 99 MBA students from a public university in China. The results of the study show that English is not extensively used in the workplaces of MBA business English students, and that the majority of them use Chinese. Most English usage occurs in foreign businesses. The most difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Some best practices of business English learning include role-play and simulation that elicit interaction or communication and build up business knowledge. Those activities allow the students to use practical content relevant to their jobs and business needs through role play, simulation, and business writing practice that will be used during the training or internship (Xie & Chen, 2019).…”
Section: Figure 1 the Design Of Blended Learning Instructionmentioning
confidence: 99%
“…Some best practices of business English learning include role-play and simulation that elicit interaction or communication and build up business knowledge. Those activities allow the students to use practical content relevant to their jobs and business needs through role play, simulation, and business writing practice that will be used during the training or internship (Xie & Chen, 2019).…”
Section: Figure 1 the Design Of Blended Learning Instructionmentioning
confidence: 99%
“…In 2018, one article (Clement & Murugavel, 2018) examined English language use among corporate employees. In addition, three articles were found from 2019 (Huang & Huang, 2019;Xie & Chen, 2019;Krishna, 2019) and 2020 (Xu, 2020;Nawaz et al, 2020;Thavabalan et al, 2020), respectively from the five databases. One relevant article (Suningsih et al, 2021) published in 2021 was identified, while two articles (Xie, 2022;Sukkrong et al, 2022) were found in 2022 respectively that examined English language in business communication.…”
Section: The Distribution Of English Users In the Business Fieldmentioning
confidence: 99%
“…In research studies on English as a Foreign Language (EFL) or English as a Second Language (ESL) contexts, researchers feel that apart from general English communicative needs fulfilment, learners in specific courses, such as vocational and training courses, need English tailor-made for their specific requirements (Evans, 2010;Hagler, 2014;Jones et al, 2017;Lu, 2015;Sun et al, 2016;Xie & Chen, 2019;Yu, 2014). In this context Basturkmen's (2010, p. 71) book based on the needs analysis of EFL/ESL learners, presents course ideas for specific English requirements, such as "English for the Police."…”
Section: Esp In Other Contextsmentioning
confidence: 99%